Answer:
-44
Step-by-step explanation:
first take -2 to the fifth power (-32) , after that take -2 to the second power (4) and then take -2 to the third power (-8). Subtract -32 and 4, then add -8 and you get your answer.
The two lines start at the same point outside the circle, using the intersecting Secants theorem, When you multiply the two dims for each line together, they are equal
For A:
5 * (5+x) = 6 * (6+4)
25 + 5x = 60
5x = 35
x = 35/5
x = 7
For B:
5 * (5+ 3) = 4 * ( 4+x)
40 = 16 + 4x
4x = 24
x = 24/4
x = 6
Answer:
<h3>
ln (e^2 + 1) - (e+ 1)</h3>
Step-by-step explanation:
Given f(x) = ln and g(x) = e^x + 1 to get f(g(2))-g(f(e)), we need to first find the composite function f(g(x)) and g(f(x)).
For f(g(x));
f(g(x)) = f(e^x + 1)
substitute x for e^x + 1 in f(x)
f(g(x)) = ln (e^x + 1)
f(g(2)) = ln (e^2 + 1)
For g(f(x));
g(f(x)) = g(ln x)
substitute x for ln x in g(x)
g(f(x)) = e^lnx + 1
g(f(x)) = x+1
g(f(e)) = e+1
f(g(2))-g(f(e)) = ln (e^2 + 1) - (e+ 1)
Answer:
A) D + Q = 50
B) .10D + .25Q = 7.10
We multiply A) by -.10
A) -.10D - .10Q = -5 then adding this to B)
B) .10D + .25Q = 7.10
.15Q = 2.10
Quarters = 14 = 3.50
Dimes = 36 = 3.60
Step-by-step explanation:
Answer:
Thus option C ...Maya wrote x/y^3 is correct